The reign of Emperor John II Komnenos, 1087-1143 - Lau, M (2015)
Despite ruling over arguably the most powerful Christian nation in the period, in a time when European and middle-eastern history entered a new phase of interaction due to the Crusades, John’s reign has received little scholarly attention. The only major monograph is Chalandon's Les Comnènes from 1912, since which a number of new sources have come to light, together with numerous studies on his contemporaries. Despite the impression that sources are lacking for his reign, in fact there are over 50,000 words of court letters and poetry that allow us to take the political pulse of the Komnenian court. When incorporated with the extra information found in Syriac, Arabic, Russian, Hungarian and many other texts, archaeological remains, sigillographic and numismatic evidence, John’s reign is in fact very well covered, and ripe for analysis. Between fieldwork in Turkey, Serbia and Kosovo and translations of these previously unused texts, this thesis contains new material on top of over a century of updated methodologies and research since Chalandon. As such, this thesis will reevaluate assumptions concerning John and his reign, including rewriting the narrative itself, which has previously been distorted due to the agendas of the few sources used. Through the reconstruction of this narrative John's empire can be reexamined, and how it operated in the changed world of the twelfth century determined. The empire found itself in a more multi-polar power dynamic, and tackled this by operating more as an empire than it had as a larger polity as in the previous century: incorporating other peoples as clients and emphasing the rhetoric of imperial piety and legitimacy of the Roman empire. Equally, all of John’s actions on the frontiers were fuel for the political theatre that was Constantinople, and this dynamic shaped his actions and resulted in the empire that Manuel inherited.